ANALISIS NILAI KARAKTER PEDULI LINGKUNGAN PADA SISWA KELAS III DI SDSI BAITURRAHMAN - Jumilah , Dessy Setyowati, Yunika Afryaningsih (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2026)
This study aims to analyze the value of environmental care character among third-grade students at SDSI Baiturrahman. The research employed a descriptive qualitative method with third-grade students as the subjects. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The analysis focused on four main indicators: maintaining classroom and school cleanliness, caring for plants, supporting the go green program, and proper waste disposal. The findings reveal that most students have developed environmental awareness, although their consistency varies. In terms of cleanliness, some students were proactive in class duties and organizing facilities, while others still required teacher guidance. Regarding plant care, several students actively maintained the garden, but some only did so when directed. The go green program fostered solidarity and responsibility, though student involvement was uneven. In waste management, students were accustomed to disposing of trash properly, but waste separation was not optimal due to limited facilities. Overall, habituation, teacher role modeling, and adequate facilities play a key role in shaping environmental care character among elementary school students.